Universidade Regional de Blumenau, Blumenau, Santa Catarina - Souza, Marco Aurelio da Cruz (2020)
The classical and contemporary dancer's training at the Bolshoi Theater School in Brazil located in Joinville (SC) is based on the rigid discipline and methodology of the Russian School. In my doctoral thesis on Human Motricity, in the Dance specialty, held at the Faculty of Human Motors in Lisbon-Portugal, I try to understand the role of the popular dance discipline in the curriculum of this school. After the data analysis, I present a methodological proposal for the teaching of popular dance that is called "Dança popular, espaço coletivo de saberes”. We believe that as a curricular component, popular dance can provide teachers the possibility of using new pedagogical strategies favoring the recognition of Brazilian culture, new creative processes, and giving "voice" to the students, increasing autonomy in the decisions made. This results in that the process of training of dancer goes parallel to the educational process, with focus on the citizen formation, and still opportunizing a process of interdisciplinarity. This reflection around the structures of the lived in the School of the Bolshoi Theater in Brazil gave rise to the proposal based on principles of art and education, generating new possibilities of working with the body from the perspective of traditional folk dance.